1991
DOI: 10.1111/j.1600-0722.1991.tb01878.x
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge augmentation in rats by Bio‐Oss

Abstract: Pinholt EM, Bang G, Haanaes HR: Alveolar ridge augmentation in rats by Bio-Oss. Scand J Dent Res 1991; 99: 154-61.Abstract -The purpose of the study was to examine if Bio-Oss initiated osteoinduction or osteoconduction when implanted into rats. Sintered and unsintered granules of the anorganic bovine bone Bio-Oss was implanted subperiosteally for alveolar ridge augmentation purposes and heterotopically in the abdominal muscles of rats. Light microscopic evaluation revealed no osteoinduction or osteoconduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 25 publications
3
66
0
2
Order By: Relevance
“…In this study, the presence of macrophages and giant cells around the particles, as observed previously (2,10), may explain the reduction of the amount of particles throughout the experimental time. On the other hand, a previous report suggested that this type of material may also be incorporated into the newly formed bone (4,5).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, the presence of macrophages and giant cells around the particles, as observed previously (2,10), may explain the reduction of the amount of particles throughout the experimental time. On the other hand, a previous report suggested that this type of material may also be incorporated into the newly formed bone (4,5).…”
Section: Discussionsupporting
confidence: 83%
“…This material was used previously for the reconstruction of alveolar ridge (2), bone loss associated to both periodontal and periapical lesions (3), on bone defects (4) and as a hemostatic agent (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, regarding the resorption of Bio-Oss, contradicting reports have emerged. On one hand, a previous study revealed that the bovine bone mineral underwent resorption 21) . On the other hand, numerous researchers claimed that the resorption process of BioOss ® was very slow [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…It may be used alone or mixed with cancellous autogenous bone for the reconstruction of limited horizontal alveolar ridge defects, for subantral bone augmentation as part of sinus lift procedures, for periodontal regeneration, and for the healing of extraction sockets. [22][23][24][25] Although only one study has reported on the development of FB of the maxillary sinus following sinus bone grafting, in recent years, we have observed a resurgence of cases presenting with such a calamitous association. 26 Thus, the present case-control study was undertaken to assess the possible association between sinus bone graft material and subsequent development of FB of the maxillary sinus.…”
mentioning
confidence: 99%